Impact of children’s purported past-life memories: a follow-up investigation of American cases - Pehlivanova, Marieta; Cozzolino, Philip J.; Tucker, Jim B. (Frontiers in Psychology, 2024)
Introduction: Some children between ages 3 and 6 claim to have memories of purported past lives. Prior research has documented this phenomenon in detail, including typical features and how it can manifest in the child's life. However, less is known about what happens to these children as they transition to adulthood and whether this childhood experience may impact their lives. Methods: We conducted the first observational follow-up study of American adults (N=23) who were originally interviewed as children regarding their claims of past-life memories. Using online surveys with validated self-report questionnaires and a phone interview, we assessed personality traits, subjective well-being, and the impact of these memories on various domains in their lives. Results: Adults who reported apparent past-life memories as children seem to lead normal, productive lives and have high educational attainment compared to the general population. They exhibit moderate-to-high levels of spiritual well-being, and slightly elevated, but not pathological, dissociation and fantasy proneness, compared to unselected samples. Sixty-five percent endorsed some impact of the purported memories in their lives, with few reporting negative effects. Spearman's correlation analysis showed that the degree of impact of this experience was positively associated with the trait of absorption. Conclusions: This study offers a first glimpse into the lives of American individuals touched by this intriguing childhood experience.